A convenient synthesis of highly luminescent lanthanide 1D-zigzag coordination chains based only on 4, 4′-bipyridine as connector. (24th November 2016) - Armelao, Lidia; Belli Dell'Amico, Daniela; Bellucci, Luca; Bottaro, Gregorio; Labella, Luca; Marchetti, Fabio; Samaritani, Simona
Graphical abstract: A rational strategy for the preparation of highly luminescent monodimensional coordination polymers (CPs) by assembling β-diketonato complexes with 4, 4′-bipyridine is reported. The syntheses proceed in mild conditions affording coordination chains which were characterized by X-ray diffraction studies. Abstract: The coordination polymers [ Ln ( β - dik ) 3 bpy ] ∞ 1 ·C7 H8 (Ln = Eu, β-dik = dbm, tta, hfac; Ln = Tb; β-dik = dbm; Hdbm = dibenzoylmethane, Htta = thenoyltrifluoroacetone, Hhfac: hexafluoroacetylacetone) were easily assembled in mild conditions and high yields starting from the anhydrous lanthanide β-diketonates as nodes and 4, 4′-bipyridine (bpy) as connector. X-ray single crystal studies have shown zigzag extended chains where lanthanide centres are 8-coordinated in a distorted square-antiprismatic geometry. Photoluminescence studies show bright red europium emission and spectral features dependent on the topology of the polymeric chains.